DNA Sensing across the Tree of Life. Issue 10 (October 2017) - Gallucci, Stefania; Maffei, Massimo E.
Abstract : From plants to mammals, pattern recognition receptors (PRRs) specifically recognize DNA, as a potential marker of either infection or damage. These receptors play critical roles in inflammation, immunity, and pathogen resistance. Importantly, given the ubiquity of DNA, its sensing must be tightly regulated. DNA localization plays a key role in recognition, as highlighted by Toll-like receptor 9 (TLR9) in the endosomal compartment and cyclic GMP–AMP synthase (cGAS) and absent in melanoma 2 (AIM2) in the cytoplasm. Sequence and structure also enhance recognition across species. Evidence in plants supports the sensing of extracellular DNA by PRRs, leading to calcium-dependent signaling, although no receptor has been definitively identified yet. Here, we review the shared and distinct features of DNA sensors, and their physiological functions, across the tree of life. Trends: DNA is a ubiquitous 'genetic library' across the tree of life, and its location and structure can be modified by host damage and infections, making it a danger signal. Accordingly, many receptors sense DNA across the tree of life, such as cGAS and TLR9 in mammals, and while there is evidence for a separate sensing system in plants, receptors await identification. DNA sensors predate in evolution the appearance of the immune system, suggesting a pivotal role for DNA sensing in immune-independent host defense. DNA sensing is critical for resistance to viral and some bacterial infections, but it has also been linked to autoimmunity, demonstrating the complex risks and benefits of relying on a ubiquitous molecule as a danger signal. Different receptors and species rely on different strategies to modulate responses and likely mitigate risks; for example, DNA localization and degradation play a critical role in mammals, while DNA fragmentation induces species-specific responses in plants.